A comparative study of aluminium and nutrient concentrations in mistletoes on aluminium‐accumulating and non‐accumulating hosts. (1st March 2013) - Scalon, M. C.; Haridasan, M.; Franco, A. C.; Amtmann, A.
Abstract Mistletoes offer a unique model to study interactions among Al and nutrients in vascular plants, because they grow and reproduce on hosts with distinct Al uptake strategies. We investigated Al distribution and nutrient relations of mistletoes on Al‐accumulating and non‐accumulating hosts. We hypothesised that mistletoes would exhibit similar leaf nutrient and Al concentrations as their host plants, but a strong compartmentalisation of Al when growing on Al‐accumulators. We measured concentrations of N, P, K, Ca, Mg, Cu, Fe, Mn, Zn in leaves and Al in leaves, seeds and branches of Phthirusa ovata and Psittacanthus robustus infecting Miconia albicans, an Al‐accumulator, and Ph. ovata infecting Byrsonima verbascifolia, a non‐Al‐accumulator. High leaf concentrations of Al in Ph. ovata only occurred while parasitizing the Al‐accumulating host; there was no accumulation in branches or seeds. In P. robustus, large concentrations of Al were found in leaves, branches and seeds. Mistletoe seed viability and leaf nutrient concentrations were not affected by Al accumulation. Passive uptake of Al, Ca, Mg, Mn and Cu in mistletoes was evidenced by significant correlations between mistletoes and host leaf concentrations, but not of N, P and K. Al was retranslocated to different plant organs in P. robustus, whereas it was mostly restricted to leaves in Ph. ovata. We suggest that Al might have some specific function in P. robustus, which only parasitizes Al‐accumulator hosts, while the host generalist Ph. ovata can be considered a facultative Al‐accumulator.